Utilization of used lubricating oil for anfo-emulsion production: A study on blasting activities in the copper mining area - Wulandari, Intan Suci (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Copper is crucial for the development of electric vehicles and renewable energy technologies. In Indonesia, PT ABC's open-pit mining operations are expanding, leading to increased waste generation, particularly used lubricating oil, which is contaminated with water and metal particles but has caloric value comparable to diesel. This study explores the potential of using this oil as a diesel substitute in explosives, focusing on economic and environmental benefits. Method: The study used data collection methods to measure the annual volume of waste oil, cost savings from using it as a fuel substitute, and compliance with hazardous waste utilization regulations. The research analyzed the impact of substituting up to 80% of diesel fuel requirements with used lubricating oil. Findings: PT ABC utilizes approximately 2,699,850 liters of used lubricating oil annually. The company achieves a 99.99% compliance rate with hazardous waste permits. Substituting up to 80% of diesel with used oil resulted in an economic gain of IDR 38,885,321,437 in 2023 and diesel procurement savings of IDR 2,473,012,791. These findings highlight the economic and environmental advantages of waste management practices in mining operations. Conclusion: The integration of used lubricating oil as an alternative fuel in mining operations reduces operational costs, enhances environmental sustainability, and aligns with circular economy principles. This approach contributes to sustainable mining practices by transforming waste into reusable resources, offering significant economic and environmental benefits. Novelty/Originality of this article: This study is original in demonstrating the use of used lubricating oil as a substitute for diesel fuel in mining, showing its potential to reduce costs, improve sustainability, and support circular economy practices in the mining sector.